2000
DOI: 10.1002/(sici)1096-8644(200002)111:2<221::aid-ajpa8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional aspects of the patterning of enamel thickness distribution in extant large-bodied hominoids

Abstract: One of the few uncontested viewpoints in studies of enamel thickness is that the molars of the African apes, Pan and Gorilla, possess "thin" enamel, while Pongo and modern humans possess varying degrees of "thick" enamel, even when interspecific differences in overall body or tooth size are taken into account. Such studies focus primarily on estimates of the total volume of enamel relative to tooth size (i.e., "relative" enamel thickness), as this is thought to bear directly on questions concerning dietary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 87 publications
(143 reference statements)
3
135
2
2
Order By: Relevance
“…The number of Retzius lines and cuspal enamel thickness were both found to be variable among cusp and molar types, which led to variation in cusp-specific crown formation times. Patterns of cuspal enamel thickness are consistent with other studies that have suggested a trend between buccal and lingual analogues, which may be due to functional differences (e.g., Reid et al, 1998a;Spears and Macho, 1998;Schwartz, 2000;Kono, 2004;Smith et al, in press). …”
Section: Variation In Incremental Developmentsupporting
confidence: 89%
See 1 more Smart Citation
“…The number of Retzius lines and cuspal enamel thickness were both found to be variable among cusp and molar types, which led to variation in cusp-specific crown formation times. Patterns of cuspal enamel thickness are consistent with other studies that have suggested a trend between buccal and lingual analogues, which may be due to functional differences (e.g., Reid et al, 1998a;Spears and Macho, 1998;Schwartz, 2000;Kono, 2004;Smith et al, in press). …”
Section: Variation In Incremental Developmentsupporting
confidence: 89%
“…Smith (2004) examined the correlation between developmental variables in this sample, in part to determine if size differences among cusps or molars may explain some of the apparent variation. Bicervical diameter was used as a size scalar, as it has been demonstrated to have a positive relationship with tooth size (and by inference, body mass) (e.g., Martin, 1983;Shellis et al, 1998;Schwartz, 2000;Grine, 2002). Several variables showed positive allometry, including periodicity, number of Retzius lines, and crown formation time.…”
Section: Variation In Incremental Developmentmentioning
confidence: 99%
“…However, Schwartz (2000a) suggested that the majority of published data on enamel thickness in modern humans are derived from European populations, which may not be representative of the species mean and may underestimate variation. A more recent investigation of enamel thickness in disparate modern human regional populations found values similar to those reported for European populations, with low levels of variation within and among populations (Grine, 2002(Grine, , 2005.…”
Section: Variation and Patterning Of Enamel Thicknessmentioning
confidence: 99%
“…Another measure that has been employed as a scalar in enamel thickness studies, the bi-cervical diameter (measured between buccal and lingual cervices in cross-sections), may be better suited for standardizing size differences among taxa. Schwartz (2000a) and Grine (2002) recently employed bi-cervical diameter as a scalar for body size (although scalars are probably not necessary for intra-specific comparisons). While bi-cervical diameter has not been directly examined in individuals of known body size, Grine (2002) demonstrated a strong positive association between dentine area and bi-cervical diameter, and Shellis et al (1998) suggested that the former scales isometrically with body size among primates.…”
Section: Implication For Scaling Of Enamel Thickness In Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation